Depression and eating styles are independently associated with dietary intake. (1st March 2019) - Paans, Nadine P.G.; Gibson-Smith, Deborah; Bot, Mariska; van Strien, Tatjana; Brouwer, Ingeborg A.; Visser, Marjolein; Penninx, Brenda W.J.H.
Abstract: Depression and eating styles are two important, interrelated factors associated with dietary intake. However, it remains unclear whether depression and eating styles are independently associated with dietary intake, and whether associations between depression and dietary intake are mediated by eating styles. Therefore, the aim of the current study was to investigate the associations of, and interplay between depression and eating styles in relation to different aspects of dietary intake. Cross-sectional data from 1442 participants (healthy controls (22.7%), remitted (61.0%) and current patients (16.3%)) from the Netherlands Study of Depression and Anxiety were used. Linear regression analyses were used to determine associations of depressive disorders (DSM-IV based psychiatric interview), self-reported depressive symptoms (Inventory of Depressive Symptomatology), emotional, external and restrained eating (Dutch Eating Behavior Questionnaire) with 4 measures of dietary intake (total energy intake (kcal/d), Mediterranean diet score (MDS), intake of sweets foods (g/d), and snack/fast-food (g/d)) measured with a 238-item food frequency questionnaire. Statistical mediation analyses were used to study whether associations between depression and dietary intake were mediated by eating styles. Current depression diagnosis and severity were associated with lower MDS and higher intake of sweet foods and snack/fast-food. Emotional and external eating were associated with higher intakes of snack/fast-food; external eating was also associated with higher total energy intake. Restrained eating was associated with lower total energy and intake of sweet foods, and higher MDS. Associations between current depression or severity and intake of snack/fast-food were mediated by external eating. In general, depression and eating styles contributed independently to poorer diet quality and higher intake of sweet and snack/fast-food. The association between depression and higher intake of snack/fast-food was mediated by external eating.